The Influence of Corporate Governance, Leverage, and Profitability on Company Value - Larasati, Dinar; Gantino, Rilla (Owner : Riset dan Jurnal Akuntansi, 2024)
This empirical research aims to determine the influence of corporate governance, leverage and profitability on company value in two company sub-sectors, namely food, beverage and telecommunications listed on the IDX in 2018-2022. The dependent variable in this research is company value. This research uses a purposive sampling model. The data analysis model used is multiple regression analysis. The results of this study state that leverage has an effect on company value in both sub-sectors, corporate governance has an effect on company value in the food and beverage sub-sector, while corporate governance has no effect on company value in the telecommunications sub-sector and profitability has no effect on company value in both company sub-sectors